2022
DOI: 10.3390/ijms23094616
|View full text |Cite
|
Sign up to set email alerts
|

The P2X7 Receptor Promotes Colorectal Inflammation and Tumorigenesis by Modulating Gut Microbiota and the Inflammasome

Abstract: Background: Given the role of the P2X7 receptor (P2X7R) in inflammatory bowel diseases (IBD), we investigated its role in the development and progression of colitis-associated colorectal cancer (CA-CRC). Methods: CA-CRC was induced in P2X7R+/+ and P2X7R−/− mice with azoxymethane (AOM) combined with dextran sodium sulfate (DSS). In a therapeutic protocol, P2X7R+/+ mice were treated with a P2X7R-selective inhibitor (A740003). Mice were evaluated with follow-up video endoscopy with endoluminal ultrasound biomicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…The role of extracellular ATP and adenosine in tumor development has not been extensively studied and related studies have provided contradictory results. For example, studies assessing the role of the ATP receptor P2X7R in inflammationassociated CRC models have described an increase as well a reduction of tumor incidence in mice deficient for P2X7R (86,87). Evidence for the involvement of ATP and adenosine in activating ILC responses was provided in the context of tissue repair and inflammation.…”
Section: Adenosine Triphosphatementioning
confidence: 99%
“…The role of extracellular ATP and adenosine in tumor development has not been extensively studied and related studies have provided contradictory results. For example, studies assessing the role of the ATP receptor P2X7R in inflammationassociated CRC models have described an increase as well a reduction of tumor incidence in mice deficient for P2X7R (86,87). Evidence for the involvement of ATP and adenosine in activating ILC responses was provided in the context of tissue repair and inflammation.…”
Section: Adenosine Triphosphatementioning
confidence: 99%
“…In a therapeutic study, P2X7R +/+ mice were treated with the P2X7R selective inhibitor A740003.Video endoscopy and endoluminal ultrasound biomicroscopy revealed histological changes in colonic tissue.Analyses showed increased accumulation of immune cells, increased proinflammatory cytokine production and upregulated NLRP3 and NLRP12 genes in P2X7R +/+ mice, which were alleviated by P2X7R inhibition. Microbial alterations in P2X7R −/− and P2X7R+/+-induced mice were partially reversed by A740003, suggesting that the interaction between P2X7R and dysbiotic microbiota signals triggers intracellular pathways, inflammasome activation and exacerbates inflammation (Bernardazzi et al, 2022) (Figure 2C). In a murine model of alcoholic liver disease (ALD), carnosic acid (CA) mitigates ethanol-triggered lipid accumulation in AML12 cells and diminishes IL-1β release by suppressing the P2X7R-NLRP3 pathway in murine peritoneal macrophages (MPM) (Zuo et al, 2023).…”
Section: Inflammatory Signaling Cascades: Connecting P2x7 Receptor To...mentioning
confidence: 99%
“…In addition, AOM/DSS treated P2X7R +/+ mice induce upregulation of the NLRP3, NLRP12, MAPK1 and IL-1β target gene in mouse model. In protein level, it enhances the expression of NF-κB and phosphorylated ERK (Bernardazzi et al, 2022). Adinolfi et al showed that the expression of P2X7R promoted the growth of colon cancer in vivo.…”
Section: The P2x7r and Digestive System Cancersmentioning
confidence: 99%